Software Implementation Research of CRC Computation Algorithms Compatible with PKZIP, WINRAR, ETHERNET; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Mytsko E. A. Evgeniy Aleksandrovich; Malchukov A. N. Andrey Nikolaevich; Kim V. L. Valery Lvovich; Osokin A. N. Aleksandr Nikolaevich; Zoev I. V. Ivan Vladimirovich; Ryzhova S. E. Svetlana Evgenievna (2016, 2016)
Title screen